2021
DOI: 10.3390/ijms222212135
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Innate Immunity in Pediatric Patients Type 1 Diabetes—Focus on Toll-like Receptors Expression

Abstract: Type 1 diabetes (DM1) is classified as an autoimmune disease. An uncontrolled response of B and T lymphocytes to the body’s own tissues develops in the absence of immune tolerance. The main aim of the study was to evaluate the effect of the duration of type 1 diabetes in children on the expression of TLR receptors and the relationship with the parameters of glycemic control in patients. As a result, we showed significant differences in the level of TLR2, TLR4 and TLR9 expression in patients with DM1 in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Here, focusing on adults with longstanding T1D, we show that they have a more active immunological profile as compared to age-matched healthy controls. Consistent with previous studies in children with established diabetes showing an increase of circulating neutrophils and a decrease of NK cells (7,24), we also observed enhanced neutrophil and diminished NK proportions in adults affected for more than 20-years with diabetes. However, in contrast to the lower circulating monocyte proportions found in paediatric patients diagnosed for less than 2-years with diabetes (27), we observed enhanced percentages and absolute numbers of monocytes in adults with longstanding T1D as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, focusing on adults with longstanding T1D, we show that they have a more active immunological profile as compared to age-matched healthy controls. Consistent with previous studies in children with established diabetes showing an increase of circulating neutrophils and a decrease of NK cells (7,24), we also observed enhanced neutrophil and diminished NK proportions in adults affected for more than 20-years with diabetes. However, in contrast to the lower circulating monocyte proportions found in paediatric patients diagnosed for less than 2-years with diabetes (27), we observed enhanced percentages and absolute numbers of monocytes in adults with longstanding T1D as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…We and others have shown that blood immune cell profiling approaches are a powerful tool for detailed characterization of immune cell subsets in peripheral blood of healthy individuals and patients (18,(22)(23)(24). The association of peripheral immune cell changes and disease progression of type 1 diabetes has been shown in several studies, especially in newly diagnosed diabetes patients (6,7,(23)(24)(25)(26). Here, focusing on adults with longstanding T1D, we show that they have a more active immunological profile as compared to age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NK cell activation occurs as a result of NKp46 fusion with unknown ligands on pancreatic b cells. The authors showed that the lack of NKp46 receptor, or blocking its activity, inhibits the development of T1DM [28,55]. Aboelnazar et al also assessed the expression of NK and NKp46+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with more advanced targeting screening tools for these endosomal targets, the arsenal of precision adjuvants available to vaccinate this vulnerable population can substantially advance. This framework can be more broadly applied to various vulnerable populations as we characterize population-specific immunity [ 50 , 51 , 52 ].…”
Section: Precision Vaccinology Principles In Adjuvant Innovation Disc...mentioning
confidence: 99%